Phosphorescent iridium (III) complex with covalent organic frameworks as scaffolds for highly selective and sensitive detection of homocysteine - Deng, Chuti; Xu, Juntong; Zhang, Qi; Fan, Yong (Frontiers in Chemistry, 2024)
It is of great interest to develop a convenient and cost-effective platform for detecting homocysteine (Hcy), which has been found as a biomarker for Alzheimer's disease, gastric cancer, and other diseases. In this study, we synthesized five phosphorescent Ir(C^N)2(N^N)+ compounds (Irn, n=1 5) with various substituents (-CHO or -CHO/-NH2), which were doped into a covalent organic framework (COF) host via covalent bonding. The resulting optimal composites (denoted as Ir4/5@EBCOF) with –CHO/-NH2 substituents not only overcome the self-quenching issue for bare Ir4/5 complexes, but also show rapid, high selective and sensitive Hcy detection, with a limit of detection (LOD) of 0.23 μM and reaction time of 88 s. The sensing mechanism was revealed by the unique cyclization reaction between Ir(III) and Hcy to form a six-membered ring. During the process, the changed color of the composites can also be viewed by the naked eye. It is envisaged that the reported phosphorescent Iridium (III) complexes with covalent organic frameworks have the potential to serve as a promising thiols-detecting platform.